2021
DOI: 10.21608/adjalexu.2021.185218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anterior Maxillary Horizontal Ridge Augmentation With Simultanous Implant Placement Using Cerabone® Versus Cerabone® Combined With Platelet Rich Plasma (Randomized Clinical Trial)

Abstract: INTRODUCTION:Rehabilitation of the anterior maxilla using dental implants is frequently problematic because of the deficiency of alveolar ridge width. Under certain conditions ridge augmentation with simultaneous implant placement is recommended. OBJECTIVES: To evaluate horizontal augmentation of narrow anterior maxillary alveolar ridge with simultaneous implant placement using Cerabone® with and without platelet rich plasma (PRP). MATERIALS AND METHODS: In this study, 14 implants were placed in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…They found that the alveolar ridge width increase from one week to four months postoperatively was statistically significant. Furthermore, Ibrahim et al 18 in their study found that PRP when mixed with xenograft had a statistically significant impact on buccal bone thickness at the sixth months postoperatively. Additionally, Eskan et al 20 conducted a randomized clinical trial in which they compared horizontal ridge augmentation using PRP mixed with allograft versus allograft alone; in both groups the graft was covered by a membrane.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…They found that the alveolar ridge width increase from one week to four months postoperatively was statistically significant. Furthermore, Ibrahim et al 18 in their study found that PRP when mixed with xenograft had a statistically significant impact on buccal bone thickness at the sixth months postoperatively. Additionally, Eskan et al 20 conducted a randomized clinical trial in which they compared horizontal ridge augmentation using PRP mixed with allograft versus allograft alone; in both groups the graft was covered by a membrane.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, Ibrahim et al 18 reported no statistically significant difference in implant stability measured by Osstell between implants placed simultaneously with horizontal ridge augmentation using xenograft mixed with PRP and those placed simultaneously with xenograft without PRP. However, they stated that there was a statistically significant difference in implant stability between immediate postoperative and six months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The implant success rate was 100% during the follow-up period [ 8 ]. Ibrahim et al [ 9 ] evaluated the augmentation of the narrow anterior maxillary alveolar ridge in a randomized clinical trial. There was new bone formation six to seven months postoperatively following xenograft placement.…”
Section: Discussionmentioning
confidence: 99%
“…The particle size of this material is 0.25 to 2 mm [9,10]. BioOss TM has been shown to be effective in sinus floor augmentation [11], socket or alveolar ridge preservation, horizontal and vertical augmentation [12,13], and peri-implant defects [14,15].…”
Section: Introductionmentioning
confidence: 99%